Analisis Algoritma Pencarian Pada Sistem Informasi Berdasarkan Kajian Literatur - Hasby Ash-Shiddiq; Frayoga Nursofyan (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
The rapid development of information technology has increased data volume and complexity in various information systems, making efficient search mechanisms essential. Search algorithms play a crucial role in determining data access speed and overall system performance. This study aims to analyze the characteristics, efficiency, and application contexts of various search algorithms in information systems. The research employs a literature review method by analyzing 15 relevant national journal articles. The results indicate that search algorithms can be classified into linear search algorithms, non-linear search algorithms based on sorted data, graph-based search algorithms, and text pattern-based search algorithms. Each algorithm has specific strengths and limitations influenced by data structure, dataset size, and system requirements. Therefore, selecting an appropriate search algorithm must consider the system context to achieve optimal efficiency and performance.